Sufism in al-Sanūsī’s (d. 895/1490) al-Manhaj al-sadīd fī sharḥ kifāyat al-murīd - Andersson, Tobias (Journal of Sufi studies, 2025)
The North African theologian Muḥammad b. Yūsuf al-Sanūsī (d. 895/1490) participated in a scholarly tradition that combined Ashʿarī kalām with Junaydī taṣawwuf, but his approach to Sufism has received little scholarly attention. This article examines how al-Sanūsī integrates Ashʿarism and Sufism in al-Manhaj al-sadīd fī sharḥ kifāyat al-murīd, also known as Sharḥ al-jazāʾiriyya, which is a commentary on a theological poem by Aḥmad b. ʿAbd Allāh al-Zawāwī al-Jazāʾirī (d. 884/1479) that concludes with a substantial section on Sufism. The article shows that al-Sanūsī systematically presents taṣawwuf as the ethical application and spiritual assimilation of the fundamental tenets of faith as defined and demonstrated in kalām. Sufism, for al-Sanūsī, is a path towards realising and embodying the Islamic creed in one’s actions, states and character traits. The article also compares al-Sanūsī’s integration of Ashʿarism and Sufism to that of his student Aḥmad Zarrūq (d. 899/1493) and highlights similarities between them, such as their common reliance on the works of al-Qushayrī (d. 465/1072), al-Ghazālī (d. 505/1111) and Ibn ʿAṭāʾ Allāh (d. 709/1309), and their theologically motivated emphasis on giving up one’s self-direction and planning (isqāṭ al-tadbīr) in deference to God as the foundation of the Sufi path.